A tunable magnetorheological electromagnetic absorber based on multiscale design and topology optimization. (5th January 2023) - Gan, Ruyi; Li, Shixu; Li, Yaping; Qi, Song; Yu, Miao
Abstract: Electromagnetic (EM) absorbers consisting of micro and macroscopic structures have attracted significant interest because of their high-performance absorption characteristics. However, difficult structural design and complex tunable methods limit the application of EM absorbers. Due to multiscale controlled property under magnetic field, magnetorheological (MR) materials can be an appropriate solution. Therefore, this paper demonstrates a tunable MR electromagnetic absorber based on multiscale design and topological optimization. Microscopically, by incorporating multi-walled carbon nanotubes (MWCNTs) into MR absorbers, the dielectric loss is reinforced while ensuring magnetic loss. Meanwhile, advanced microcomputed tomography (μ-CT) illustrates that applied ball milling and magnetic field can effectively design the particles and microstructures, enhancing the absorption and attenuation characteristics. Macroscopically, based on EM parameters, the thickness and mass can be reduced while improving the absorption property through topology optimization. The results show that the peak value of reflection loss ( RL min ) can reach −19.04 dB and effective absorption bandwidth (EAB, RL below −10 dB) reach 6.72 GHz with a thickness of 2.6 mm and magnetic flux density up to 563 mT. In addition, based on the thermoplastic characteristics of MR absorbers, the multiscale structures can be reconfigured under the combined effect of thermal and magnetic field, achieving tunable absorption properties. The results demonstrate that RL min still achieved −9.33 dB after three reconfigurations. This work not only provides a strategy for multiscale structural design of EM absorbers, but also offers an efficient and convenient method for preparation with high-performance and tunable MR absorbers. Graphical abstract: Image 1